Investigating the effect of Icaritin on hepatocellular carcinoma based on network pharmacology - Xue, Zhong; Zhang, Fan; Xu, Shaohua; Chen, Minyong; Wang, Mingzuo; Wang, Ming; Ke, Fayong; Chen, Zhaoshuo; Zhang, Mingji (Frontiers in Pharmacology, 2023)
Hepatocellular carcinoma is one of the cancers that kill people in the global population. Icaritin, a small molecule drug approved by CFDA, has demonstrated potential anti-HCC effects. However, its underlying molecular mechanisms remain unclear. We employed a multi-omics approach in this study, ,including pharmaco-omics and proteomics, to look into the Icaritin's possible molecular targets and workings in the therapy of HCC. Through pharmaco-omics analysis, we identified ten putative target genes of Icaritin, including FYN. The relationship between Icaritin and these target genes, particularly FYN, was further validated through in vitro and in vivo experiments. The outcomes revealed that Icaritin may exert its anti-HCC effects through modulating the FYN gene, highlighting the importance of multi-omics approaches in drug discovery research. This research gives valuable insights regarding the therapeutic potential of Icaritin against HCC and its possible molecular mechanisms.